Proceedings of the 10th International Conference on Human Computer Interaction With Mobile Devices and Services 2008
DOI: 10.1145/1409240.1409287
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of predictive text and speech inputs in a multimodal mobile route guidance application

Abstract: We present initial results from an evaluation of a multimodal interface for a mobile route guidance application providing public transport information in Finland. The application includes a range of input and output modalities, such as speech input and output, a fisheye GUI, and contextual predictive text input. The application has been in public pilot use for almost a year. In this paper we present results from a formal user evaluation, focusing on predictive text input and speech input and output. Speech inp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…Speech recognition was, in fact, quite robust, with overall accuracy of 93%, and 97% when OOV sentences are removed. However, as previous studies in similar multimodal conditions have shown, there is no clear correlation between the speech recognition accuracy and user experience [5], which is the case here as well. More importantly, our results show that grammar-based recognition, i.e., so-called restricted speech, can be used efficiently in this domain without user training.…”
Section: Conclusion and Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Speech recognition was, in fact, quite robust, with overall accuracy of 93%, and 97% when OOV sentences are removed. However, as previous studies in similar multimodal conditions have shown, there is no clear correlation between the speech recognition accuracy and user experience [5], which is the case here as well. More importantly, our results show that grammar-based recognition, i.e., so-called restricted speech, can be used efficiently in this domain without user training.…”
Section: Conclusion and Discussionsupporting
confidence: 52%
“…A comparison to results from a previous study with the same experimental setup and a similar mobile application [5] shows that even if the expectations for speech input are mostly the same, the user experience of speech input observed in this study is superior, particularly when future use is considered. One reason for this is that in this scenario users found the speech input to provide additional benefit to the interaction that the other modalities could not easily offer, especially when issuing more complex commands.…”
Section: Conclusion and Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Some studies explored speech as an input mechanism for mobile text entry [2,11]. General findings reveal that speech is an attractive alternative for text input.…”
Section: ) Alternative Modalitiesmentioning
confidence: 99%
“…There have been some studies on multimodal interfaces for mobile devices or applications (e.g., Melto et al, 2008). Voice-enabled interfaces are widely available in modern cell phones, which have evolved from speaker-dependent name dialing that requires user enrollment of frequently dialed names, to speaker-independent features such as continuous digit dialing, command and control, and name dialing directly from the phone's contacts directory.…”
Section: Voice-enabled Interfacesmentioning
confidence: 99%